DRY MATTER AND WATER INTAKE IN LACTATING MURRAH BUFFALOES (Indian Journal of Animal Production and Management, 2014)
The study was conducted on 18 lactating Murrah buffaloes to know the effect of different regime of watering on water intake and dry matter intake( DMI). The different regime of watering were as group-I ad lib watering, group-II, watering before 1hr of milking, group III, watering after 1 hr of milking and group-IV, watering before and after 1hr of milking. The overall DMI (kg/day/animal) for the experimental group was 12.22± 0.06 12.15±0.06, 11.73±0.06 and11.30±0.06 in group IV II, III & I respectively. The statistically the overall DMI significantly (P
Keywords: Lactating murrah buffaloes; water intake; dry matter intake